Burden and attributable risk factors of ischemic stroke in China from 1990 to 2019: an analysis from the Global Burden of Disease Study 2019 - Ye, Yang; Zhu, Yu-Tian; Zhang, Jia-Cheng; Zhang, Hao-Lin; Fan, Rui-Wen; Jin, Yu-Xin; Hu, Hang-Qi; Xin, Xi-Yan; Li, Dong (Frontiers in Neurology, 2023)
Background: The epidemiologic characteristics and attributable risk factors of ischemic stroke in China have changed over the past three decades. An up-to-date analysis on deaths, disability-adjusted life-years (DALYs), prevalence, incidence, and attributable risk factors of ischemic stroke for China is needed. This study aims to provide a comprehensive analysis of burden and attributable risk factors of ischemic stroke at national level in China by sex from 1990 to 2019. Methods: This is a secondary analysis of the Global Burden of Disease (GBD) study 2019. All data used in this study was derived from the 2019 GBD study. Deaths, DALYs, prevalence, incidence, and attributable risk factors of ischemic stroke in China by sex from 1990 to 2019 were analyzed. Results: From 1990 to 2019, the age-standardized deaths rate decreased by 3.3%, age-standardized DALYs rate decreased by 4%, age-standardized prevalence rate increased by 33.5%, and age-standardized incidence rate of ischemic stroke in China increased by 34.7%. In 2019, ambient particulate matter pollution became an important risk factor, whereas household air pollution from solid fuels was no longer a major risk factor for ischemic stroke in China. Burden of ischemic stroke was higher in China compared to other regions. Ambient particulate matter pollution among men, and diet high in sodium, smoking, household air pollution from solid fuels among women account for the increased deaths/DALYs due to ischemic stroke in China. Conclusions: Our study revealed that great changes have occurred in burden and attributable risk factors of ischemic stroke in China in the past three decades. Distinct sex-specific differences are observed in burden and attributable risk factors.